The Age of Prosumerism: Some Micro-Economic Analysis - Alderete,María Verónica (Universidad de Talca, 2017)
Abstract: Many users or consumers now operate the two sides of the market as consumers and producers. They are known as prosumers. Their presence is changing the economic dynamic. This paper develops two models, the prosumerism model that determines the prosumer equilibrium; the amount of the private good and prosumer good. The second one is the customization model based on the principal agent framework, where the principal is the manufacturer innovator and the agent the user. Results obtained predict abundance of the prosumer good in the prosumerism model and that the most innovative users will have a higher level of participation in the value creation process than the less innovative ones in the customization model. Hence, policy should encourage users’ participation in the value creation and innovation processes to achieve a higher social welfare.